Escola pública: todas as gentes cabem lá! com a palavra, os estudantes - Batista, Gilson Borsato (2022)
Schools are spaces for interaction and learning about oneself and others. Therefore, it is in their daily lives that alienating or emancipatory educational practices are established. Soon we consider knowing the Gustavo Barroso state public school, from the way students understand it. Thus, the object of study of this research is the Escola Estadual Gustavo Barroso and we seek to answer what this place is from the reading of a group of students who live in this space. Its general objective is to understand how students at Escola Gustavo Barroso understand the school space and the relationships that exist there. As a specific objective, it aims to identify how students conceive the school, their teachers, their colleagues and the other professionals who work there. We understand that many of the students at that school are in a moment of eagerness due to the removal from school, caused by the COVID 19 pandemic, which fostered in the educational environment, causes an uneasy social coexistence with their peers, teachers and family members. The methodology used was qualitative and, through an ethnographic approach, it mapped, together with the students, how they live, understand and understand the educational institution and the professionals who work there. Data collection took place through questionnaires, analysis of school documentation, interviews and conversation circles. Having as a theoretical reference, the foundation in Dubet (2003a, 2003b, 2008); Charlot (2000, 2001); Freire (1996, 2011, 2013); Masschelein e Simons (2017).